2020
DOI: 10.1111/jgh.15186
|View full text |Cite
|
Sign up to set email alerts
|

Can prophylactic argon plasma coagulation reduce delayed post‐papillectomy bleeding? A prospective multicenter trial

Abstract: Background and Aim Endoscopic post‐papillectomy bleeding occurs in 3% to 20% of the cases, and delayed bleeding is also problematic. However, there is no consensus on how to reduce delayed post‐papillectomy bleeding. The aim of this study was to evaluate the efficacy of prophylactic argon plasma coagulation (APC) to minimize delayed bleeding and reduce the persistence of residual tumors after endoscopic papillectomy. Methods In a prospective pilot study of patients with benign ampullary tumors, the prophylacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Our results showed that most adverse events caused by EP showed mild- to moderate-grade severity. The role of thermal ablation in bleeding remains controversial and studies have shown that the risk of pancreatitis increased with the size of the lesion and when hemostasis was performed[ 22 , 23 , 28 ]. Here, thermal ablation was not significantly associated with bleeding or recurrence although it increased the risk of pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that most adverse events caused by EP showed mild- to moderate-grade severity. The role of thermal ablation in bleeding remains controversial and studies have shown that the risk of pancreatitis increased with the size of the lesion and when hemostasis was performed[ 22 , 23 , 28 ]. Here, thermal ablation was not significantly associated with bleeding or recurrence although it increased the risk of pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…The delayed bleeding rate was significantly lower in the APC group compared to the non-APC group (7.3 % vs. 31.7 %, OR 0.180, P < 0.01). However, there are conflicting data: a recent RCT including 54 patients failed to find any reduction in the rate of delayed postpapillectomy bleeding with APC (30.8 % in the prophylactic APC group vs. 21.4 % in the non-APC group; P = 0.434) [173]. Ismail et al [153] reported retrospectively that bleeding occurred post-papillectomy in 11/61 (18 %) despite prophylactic APC having been performed in 10/11 of those who bled.…”
Section: Prevention and Management Of Adverse Events After Endoscopicmentioning
confidence: 99%
“…A RCT has suggested that, compared with the Autocut mode, the Endocut mode may prevent immediate but not delayed bleeding in cases with tumors > 14 mm; it causes more frequent crush artifacts 118 . Prophylactic argon plasma coagulation has been reported as effective in a retrospective study (n = 82) and ineffective in a RCT (n = 54) to prevent post-ampullectomy bleeding 119 120 . Submucosal injection prior to ampullectomy did not prevent bleeding in a RCT (n = 50) and a retrospective matched cohort analysis (n = 50) 121 122 ; furthermore it was associated with higher tumor recurrence rate and a shorter recurrence-free survival in the retrospective study 121 .…”
Section: Endoscopic Proceduresmentioning
confidence: 99%